Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015 International Symposium on Network Coding (NetCod) 2015
DOI: 10.1109/netcod.2015.7176779
|View full text |Cite
|
Sign up to set email alerts
|

Delay reduction in multi-hop device-to-device communication using network coding

Abstract: This paper considers the problem of reducing the broadcast delay of wireless networks using instantly decodable network coding (IDNC) based device-to-device (D2D) communications. In D2D-enabled networks, devices help hasten the recovery of the lost packets of devices in their transmission range by sending network coded packets. To solve the problem, the different events occurring at each device are identified so as to derive an expression for the probability distribution of the decoding delay. The joint optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Not only they should use solely the packets they hold but also they can target only the users in their transmission range. For each user i in the network, the authors in [179] proposes a graph formulation ,similar to the local G-IDNC graphs, that is able to generate coding combinations only from the packets it holds and intended to users in its transmission range. As we will explain in the next section, the transmission range of users changes with the set of the transmitting users since, depending on this set, a subset of users will be in interference and cannot be targeted by any other user.…”
Section: Local Graph Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only they should use solely the packets they hold but also they can target only the users in their transmission range. For each user i in the network, the authors in [179] proposes a graph formulation ,similar to the local G-IDNC graphs, that is able to generate coding combinations only from the packets it holds and intended to users in its transmission range. As we will explain in the next section, the transmission range of users changes with the set of the transmitting users since, depending on this set, a subset of users will be in interference and cannot be targeted by any other user.…”
Section: Local Graph Representationmentioning
confidence: 99%
“…Douik et al [179] investigated the problem of minimizing the decoding delay in CDE enabled PC-D2D network. After defining the cooperative decoding delay, the authors identified the expression of the decoding delay increment of all users in the network in order to formulate the cooperative decoding delay minimization problem.…”
Section: Decoding Delay Problemmentioning
confidence: 99%
“…In other words, once a clique is chosen according to (13) among the vertices representing users in the highly critical set P(t), there may exist vertices belonging to other users that can form an even bigger clique. Thus, adding these vertices to the clique and serving this user will benefit them without affecting the IDNC constraint for the users belonging to P(t).…”
Section: A Maximum Weight Clique Solutionmentioning
confidence: 99%
“…The paper considers that algorithm whose steps can be found in [33]. This section suggests defining the objective function φ so as to both minimize the critical criterion (13) and to improve the approximation in (9) using a same method like the one in the previous heuristic.…”
Section: B Binary Particle Swarm Optimization Solutionmentioning
confidence: 99%
See 1 more Smart Citation